2020
DOI: 10.1039/c9ra09131a
|View full text |Cite
|
Sign up to set email alerts
|

Resistance hysteresis correlated with synchrotron radiation surface studies in atomic sp2 layers of carbon synthesized on ferroelectric (001) lead zirconate titanate in an ultrahigh vacuum

Abstract: Graphene-like layers synthesized in ultrahigh vacuum, characterized by surface science techniques, exhibit resistance hysteresis depending on the carbon coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Such line shape function was introduced by Joyce et al [24], and it seems to be suitable for practical uses in the spectral data such as C 1s spectra e.g [25]. Here, the scale parameter, γ, specifies the half-width at halfmaximum (HWHM) of the distribution.…”
Section: The Fitting Modelsmentioning
confidence: 99%
“…Such line shape function was introduced by Joyce et al [24], and it seems to be suitable for practical uses in the spectral data such as C 1s spectra e.g [25]. Here, the scale parameter, γ, specifies the half-width at halfmaximum (HWHM) of the distribution.…”
Section: The Fitting Modelsmentioning
confidence: 99%
“…In order to solve these problems, field-effect transistors based on graphene/ferroelectric have attracted much attention. Unlike traditional SiO 2 substrates, ferroelectric films with considerable dielectric constants can induce high levels of electrostatic doping by using a low gate voltage, and the tunable ferroelectric polarization can lead to different stable resistance states in graphene [17][18][19][20][21][22][23][24][25][26][27]. In 2009, Zheng et al [17] studied the graphene upon polyvinylidene fluoride trifluoroethylene (P(VDF-TrFE)) organic ferroelectric films, and found that controlling the ferroelectric polarization using a gate voltage would change the electrostatic doping level in graphene, thus a bistable state of high and low resistance was realized.…”
Section: Introductionmentioning
confidence: 99%